The exotic rust fungus Puccinia abrupta var. partheniicola on the invasive alien weed Parthenium hysterophorus in India: rediscovery and first report of an epiphytotic - Prakya Sreerama Kumar (CABI Agriculture and Bioscience)
Abstract Puccinia abrupta var. partheniicola, the so-called winter rust of parthenium weed (Parthenium hysterophorus), an invasive alien weed in India, was rediscovered at an epiphytotic scale in February 2023 following a prolonged period of presumed absence in the field. Disease incidence was 80–90% in large tracts of P. hysterophorus stands along the roadsides in an area of 5 km2 near Attibele–Sarjapura road (948A) in Anekal taluk of Bengaluru Urban district in Karnataka. Pycnial, aecial or telial stages of the rust were not found. The morphological parameters of uredinia and urediniospores completely matched those originally described, thus confirming the fungal identity. The significance of this rust epiphytotic to P. hysterophorus biocontrol in India is discussed together with the planned follow-up activities.